2013
DOI: 10.1002/chem.201301889
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Inherent Electrochemistry of Graphene Oxides Prepared Using Permanganate Oxidants

Abstract: Graphene and graphene oxides are materials of significant interest in electrochemical devices such as supercapacitors, batteries, fuel cells, and sensors. Graphene oxides and reduced graphenes are typically prepared by oxidizing graphite in strong mineral acid mixtures with chlorate (Staudenmaier, Hofmann) or permanganate (Hummers, Tour) oxidants. Herein, we reveal that graphene oxides pose inherent electrochemistry, that is, they can be oxidized or reduced at relatively mild potentials (within the range ±1 V)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 67 publications
(232 reference statements)
6
102
0
Order By: Relevance
“…The study was carried out as graphene oxide [30] and various reduced graphenes [31] (even in nanoscale dimensions [32,33]) have been known to exhibit significant inherent electrochemistry with oxygen-containing groups being oxidized or reduced electrochemically. [34] Figure 3A shows cyclic voltammograms at BPPG electrodes modified with the respective quantum dots in 50 mM phosphate buffer solution (pH 7.2). It is observed that the C-QDs generated a small inherent anodic signal at ~0.4 V (vs. Ag/AgCl); this oxidation signal is most likely attributed to the quinone-like functionalities at the surface of C-QDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was carried out as graphene oxide [30] and various reduced graphenes [31] (even in nanoscale dimensions [32,33]) have been known to exhibit significant inherent electrochemistry with oxygen-containing groups being oxidized or reduced electrochemically. [34] Figure 3A shows cyclic voltammograms at BPPG electrodes modified with the respective quantum dots in 50 mM phosphate buffer solution (pH 7.2). It is observed that the C-QDs generated a small inherent anodic signal at ~0.4 V (vs. Ag/AgCl); this oxidation signal is most likely attributed to the quinone-like functionalities at the surface of C-QDs.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the C-QDs generated a small inherent anodic signal at ~0.4 V (vs. Ag/AgCl); this oxidation signal is most likely attributed to the quinone-like functionalities at the surface of C-QDs. [34] G-QDs, on the other hand, exhibited featureless voltammograms, as denoted by the decomposition of electrolyte at ~+1.1 V and the reduction of protons at potentials lower than -1.0 V. Subsequently, the heterogeneous electron transfer (HET) rates of the materials were then put in comparison against the bare EPPG surface using a redox probe, potassium ferro/ferricyanide. As exemplified in Figure 3B, the electrode surface modified with C-QDs generated the largest signals, with the smallest peak-to-peak separation (ΔE p-p ) of 826 mV.…”
Section: Resultsmentioning
confidence: 99%
“…GO prepared by different preparation methods also exhibits different reduction potentials, which might be related to the oxidizing agent used in the preparation. While GO prepared with potassium chlorate as an oxidizing agent exhibits a reduction peak at À1.2 V. Three distinctive waves, reflecting the different oxygen functional groups, are observed for GO prepared by potassium permanganate [103]. For graphite oxide, the reduction potential (vs Ag/AgCl) of the peroxide group at À0.7 V, aldehyde at À1.0 V, epoxide at À1.5 V, and carboxyl group at À2.0 V, epoxide about À1.5 V, and carboxyl group about À2.0 V has been confirmed [104].…”
Section: Electrochemistry Of Graphenementioning
confidence: 92%
“…Herein, we moved a step further by assembling two different full cell supercapacitors containing both partially reduced graphite oxide (prGrO) 20 containing a majority of quinone groups 21 and a Lig/PEDOT biopolymer as electrodes. In the rst assembly, prGrO and Lig/PEDOT are used in an asymmetric device as negative and positive electrodes, respectively.…”
Section: 8mentioning
confidence: 99%
“…The presence of a majority of quinone groups in this kind of graphite oxide was already reported by Eng et al, who noticed that quinone/ hydroquinone functionalities are the likely source of the redox reactions observed in graphene oxide prepared by the MarcanoTour method. 21 Eng et al showed that this kind of GrO presents a dominant peak assigned to C-O groups with a C/O ratio of around 1.9 caused by the high degree of oxidation. Based on these quinone/hydroquinone functionalities and on their different peak potentials, Lig/PEDOT and prGrO were characterized electrochemically for use as electrodes in full-cell supercapacitors.…”
mentioning
confidence: 99%